Manufacturing of Filament for 4D Printing through Polyether-Type TPU/PLA Blend - Eun Joo Shin; Ye Jin Song; Yang Sook Jung; Imjoo Jung; Sunhee Lee (Advances in Polymer Technology)
Reversible deformation structure fabricated by 4D printing can be applied in various fields, such as actuators, intelligent mechanisms, and soft robots. In this study, 4D filaments for use in fused deposition modeling (FDM) 3D printers were fabricated by melt extrusion process mixing polylactic acid (PLA) and soft actuator grade thermoplastic polyurethane (TPU) 75 Shore A. The morphological (scanning electron microscopy, atomic force microscopy), chemical (Fourier transform infrared), thermal (differential scanning calorimetry, dynamic mechanical analysis, thermogravimetric analysis), mechanical (Instron), and WAXS properties of the prepared TPU/PLA blend (5 : 5, 7 : 3, 9 : 1) filaments were investigated. Filaments of 4D auxetic reentrant TPU/PLA samples were 3D printed, and their shape-memory characteristics were assessed at temperatures of 60°C (corresponding to the glass transition temperature of PLA), 70°C, 80°C (matching the melting temperature of the soft segment of TPU), and 90°C. The properties of TPU/PLA samples differ based on the PLA to TPU ratio, with an increase in TPU content resulting in a higher shape setting temperature but a shorter shape recovery time. For the TPU/PLA 5 : 5 sample, setting at 70°C and recovering at 85°C is the most suitable condition for shape recovery, whereas for the TPU/PLA 7 : 3 sample the best conditions are setting at 80°C and recovering at 95°C. In the case of TPU/PLA 9 : 1, shape setting is possible at 90°C, and shape recovery is fastest at 95°C. A 4D structure of TPU/PLA could be achieved based on shape memory testing by temperature stimulation of 3D printed auxetic c TPU/PLA samples.